Keefektifan Metode Fitoremidiasi Menggunakan Tanaman Eceng Gondok Untuk Menurunkan Kadar Phosphate Limbah Rumah Sakit PKU Muhammadiyah Surakarta - Munajad, Mr Fatta Yasin; , Heru Subaris K, SKM., M.Kes; , Dwi Astuti, SKM., M.Kes (2015)
Liquid waste containing phosphate substances can affect human health and the environment. Phosphate levels based on preliminary test results will be undertaken at the Hospital of PKU Muhammadiyah Surakarta of 11.544 mg / l, the results exceeded the water quality standard of waste. One way to do is to use the method fitoremidiasi with water hyacinth plants. The purpose of this study was to determine the effectiveness of the water hyacinth plant to reduce phosphate levels in PKU Muhammadiyah Hospital in Surakarta. This type of research study design true experiment with pretest and posttest with control group. Location of research at the Hospital of PKU Muhammadiyah Surakarta. Phytoremediation uses plants 4, 6 plants, and 8 plants hyacinth done for 7 days in 15 liters of waste water. Average yield - average effectiveness of phosphate levels after treatment are 94.513%, 97.976% and 99.901%. The statistical test used is the One Way Anova. The results of the study obtained plants water hyacinth effective to reduce the phosphate on the water waste debgab doses effective 8 plants (p-value 0,001). Advised on other researchers to conduct similar research using other types of aquatic plants for phosphate parameter.